Efektivitas Video dalam Meningkatkan Komunikasi Terapeutik Mahasiswa - Hendra Priyatnanto; Sri Sundari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the effectiveness of video in improving students' therapeutic communication. The method used is a literature review study utilizing several databases such as PubMed, Proquest and Google Scholar. The results showed that students' therapeutic communication increased after using video. In conclusion, therapeutic communication can effectively improve students' knowledge, attitudes, skills after education and skills about therapeutic communication. Keywords: Therapeutic Communication, Students, Video